Belonging and the Charter of Transdisciplinarity in International STEM Research - Ruttenberg-Rozen, Robyn; Leggett-Robinson, Pamela M.; Majola, Xoliswa; Ndevu, Zwelinzima; L. Powell, Nichole; Sullivan, Sabryna; Thakur, Surendra; Wilson, Gregory (Encounters in Theory and History of Education / Rencontres en Théorie et Histoire de l'Éducation / Encuentros en Teoría e Historia de la Educación)

(untitled) (Faculty of Education, Queen's University, 2025)
This paper examines the lived realities of conducting a purposefully transdisciplinary, equity-focused international STEM research project during the COVID-19 pandemic. Using the Charter of Transdisciplinarity as an analytic lens, we explore how our team navigated visa delays, shifting political contexts, administrative turnover, and digital inequities while supporting marginalized undergraduate women in STEM. Through reflective prompts and critical event analysis, we show how belonging—understood as an active, ongoing practice—enabled us to move beyond disciplinary boundaries and confront entrenched forms of marginalization in STEM and academia. Technology simultaneously connected and divided us, requiring continual renegotiation of community membership. Dialogues around artificial intelligence served as key moments of transcultural exchange and vulnerability. We argue that transdisciplinarity is a human and relational endeavor that must be intentionally cultivated. Within STEM, it emerges not from the acronym itself but from practices that center humanity, resist othering, and foster collective flourishing.